2021
DOI: 10.1371/journal.pone.0254944
|View full text |Cite
|
Sign up to set email alerts
|

A structure-based engineering approach to abrogate pre-existing antibody binding to biotherapeutics

Abstract: Development of biotherapeutics is hampered by the inherent risk of immunogenicity, which requires extensive clinical assessment and possible re-engineering efforts for mitigation. The focus in the pre-clinical phase is to determine the likelihood of developing treatment-emergent anti-drug antibodies (TE-ADA) and presence of pre-existing ADA in drug-naïve individuals as risk-profiling strategies. Pre-existing ADAs are routinely identified during clinical immunogenicity assessment, but their origin and impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Ahmed et al previously showed, through sequence and structural analysis, that non-redundant physicochemical descriptors can be used to flag Fv regions of antibodies for medicine-likeness. 203 There are numerous ways computer-aided drug design can contribute to the marketed antibody-based biotherapeutic landscape, 204 including sequence analysis (for example, see Figures S3 (a, b)), 205 structure analysis, 206 and machine learning. 207 …”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al previously showed, through sequence and structural analysis, that non-redundant physicochemical descriptors can be used to flag Fv regions of antibodies for medicine-likeness. 203 There are numerous ways computer-aided drug design can contribute to the marketed antibody-based biotherapeutic landscape, 204 including sequence analysis (for example, see Figures S3 (a, b)), 205 structure analysis, 206 and machine learning. 207 …”
Section: Discussionmentioning
confidence: 99%
“…47 A structurebased engineering approach has been used to abrogate pre-existing ADAs binding to the neoepitope of antibody fragments by small modifications, while maintaining favorable developability characteristics. 48…”
Section: Open Accessmentioning
confidence: 99%
“…Studying the interaction and affinity between V H H and its target of interest was the major goal of these papers. Additional experimental information allowed refining the models and/or docking, e.g., V H H anti-MMP8 second poses were considered better in regards to ELISA data [ 121 ] and the development of a structure-based engineering approach to abrogate pre-existing antibody binding in Biotherapeutics [ 123 ]. Regarding the actual sanitary context, Modeller was used for the design of a V H H that neutralised SARS-CoV-2.…”
Section: V H H Modellingmentioning
confidence: 99%